The Analysis of Semantic Meaning Found on Emma Watson’s Speech - Alex Martinius (PRAGMATICA : Journal of Linguistics and Literature, 2023)
The purpose of this research was to identify the types of semantic meaning contained in the speech delivered by Emma Watson to the United Nation on gender equality. The types of meaning used in this research were taken from Leech's theory, concerning seven types of meaning in semantics, namely conceptual meaning, connotative meaning, social meaning, affective meaning, reflective meaning, collocative meaning and thematic meaning. The data in this research were in the form of phrases, clauses, and sentences contained in the speech delivered by Emma Watson which was obtained by the method of collecting data through observation. Using the observation method, the results showed that there were conceptual meanings, connotative meanings, social meanings, affective meanings, reflective meanings and thematic meanings in the speech delivered by Emma Watson to the United Nation. Where the connotative meaning was the dominant meaning found in the speech (26.25%). The speech contained Emma Watson's opinion on gender equality and feminism in the world community. This research was aimed at avoiding any misperceptions in responding to the speech delivered by Emma Watson.